CONTRIBUTION OF SOME NIGERIAN ARTISTS IN TERTIARY INSTITUTIONAL ADMINISTRATION - Rom Kalilu, Razaq Olatunde; Odeniyi, Akinkunmi Olatunbosun (ISI Press Institut Seni Indonesia Surakarta, 2024)
Modern Nigerian Art emerged as a result of the efforts of artists. The later generation artists, particularly those with significant contributions to visual arts departments in Nigerian Universities deserve adequate scholastic attention. This study is a biographical examination of selected Nigerian artists who function in professional, academic, and administrative capacities in visual art departments in Nigerian universities. Eleven academics who are pioneers, administrators, and sustainers of visual arts departments in Nigerian universities were selected for biographical study based on set criteria. Findings revealed that these academics are material to the establishment, development, and sustenance of their visual art departments and Nigerian visual arts, as heads of department, deans of faculty, heads of university, visiting lecturers, lecturers on sabbatical leave, external examiners, academic assessors, resource persons in programme audit and accreditation exercise, and consultants on the establishment of visual art departments.